Acute effects of multi-walled carbon nanotubes on primary bronchial epithelial cells from COPD patients. Issue 7 (9th August 2018) - Beyeler, Seraina; Chortarea, Savvina; Rothen-Rutishauser, Barbara; Petri-Fink, Alke; Wick, Peter; Tschanz, Stefan A.; von Garnier, Christophe; Blank, Fabian
Abstract: The risks of occupational exposure during handling of multi-walled carbon nanotubes (MWCNTs) have received limited attention to date, in particular for potentially susceptible individuals with highly prevalent chronic obstructive pulmonary disease (COPD). In this in vitro study, we simulated acute inhalation of MWCNTs employing an air–liquid interface cell exposure (ALICE) system: primary human bronchial epithelial cells from COPD patients and healthy donors (controls), cultured at the air–liquid interface (ALI) were exposed to MWCNTs. To study acute health effects on the respiratory epithelium, two different concentrations (0.16; 0.34 µg/cm 2 ) of MWCNTs were aerosolized onto cell cultures followed by analysis after 24 h. Following MWCNT exposure, epithelial integrity and differentiation remained intact. Electron microscopy analyses identified MWCNTs both extra- and intracellular within vesicles of mucus producing cells. In both COPD and healthy control cultures, MWCNTs neither caused increased release of lactate dehydrogenase (LDH), nor alterations in inflammatory responses, as measured by RNA expression and protein secretion of the cytokines IL-6, IL-8, CXCL10, IL-1β and TGF-β and oxidative stress markers HMOX-1 and SOD-2. No short-term alteration of epithelial cell function, as determined by ciliary beating frequency (CBF), occurred in any of the conditions tested. In conclusion, the present study provided a reliable and realistic in vitro acute-exposure model of the respiratory tract, responsive to positive controls such as Dörentruper Quartz (DQ12) and asbestos. Acute exposure to MWCNTs did not affect epithelial integrity, nor induce increased cell death, apoptosis or inflammatory changes.